Global dynamics of a fourth-order parabolic equation describing crystal surface growth - Duan, Ning; Xu, Xianyun (Nonlinear Analysis: Modelling and Control, 2019)
In this paper, we study the global dynamics for the solution semiflow of a fourth-order parabolic equation describing crystal surface growth. We show that the equation has a global attractor in H4per(Ω) when the initial value belongs to H1per(Ω).
Keywords: global dynamics; fourth-order parabolic equation; absorbing set